Influence of disease activity on RA treatment choices in countries with restricted access to expensive, innovative drugs: a discrete choice experiment among rheumatologists. Issue 2 (4th September 2017) - Hifinger, Monika; Hiligsmann, Mickael; Ramiro, Sofia; Watson, Verity; Berghea, Florian; Péntek, Márta; Keat, Andrew; Severens, Johan L; Fautrel, Bruno; Boonen, Annelies
Abstract : Objective: To assess the influence of disease activity of patients with rheumatoid arthritis on treatment choices of rheumatologists in countries with restricted access to expensive, innovative drugs. Methods: Rheumatologists from Hungary, Romania and UK were invited to complete two consecutive discrete choice experiments with hypothetical drug treatments for two different patient profiles: high and moderate disease activity. Rheumatologists were asked to choose repeatedly between two unlabelled treatment options that differed in five attributes: efficacy (expected improvement and achieved disease activity state), safety (probability of serious adverse events), patient's preference (level of agreement), total medication costs and cost-effectiveness. A heteroscedastic discrete choice model using interaction terms between attribute levels and patient profiles (binary variable) was used to assess the preferences of rheumatologists towards each attribute and the influence of the patient profile. Results: Overall, 148 rheumatologists completed the survey (46% females, mean age 49 years, 49% academic). For both patient profiles, efficacy dominated the treatment choice over patient's preference, safety and economic aspects. However, for patients with high compared with moderate disease activity, the importance of drug efficacy significantly increased (from 48% for moderate to 57% for high disease activity), whereas the importance of patient's preference significantly decreased (from 15% to 11%). No significant differences were observed for economic and safety considerations. Conclusion: Rheumatologists were willing to give up some efficacy to account for patient's preference when choosing treatments for patients with moderate compared to high disease activity. Disease activity however did not influence importance of economic aspects in treatment choices.